Fatigue Resistant Aerogel/Hydrogel Nanostructured Hybrid for Highly Sensitive and Ultrabroad Pressure Sensing (Small 1/2022). Issue 1 (5th January 2022) - Huang, Jiankun; Zeng, Jingbin; Zhang, Xue; Guo, Gengchen; Liu, Rui; Yan, Zifeng; Yin, Yadong
Abstract : High‐Resolution Sensing In article number 2104706, Jingbin Zeng, Zifeng Yan, Yadong Yin, and co‐workers fabricate a hybrid pressure aerogel/hydrogel sensor by integrating a polypyrrole nanotube‐structured aerogel into a polyacrylamide hydrogel. With high stretchability and self‐healing property, the hybrid polymer sensor exhibits stable performance in high‐resolution sensing of a wide range of pressure from human physiological signals to significant stress caused by car rolling.